Which is the best supply chain for perishable fruits, Lean or Agile? (2018)
It is estimated that one-third of global fruit production is lost or damaged. In developing countries, post-harvest losses that often exceed 50%, together with the growth of global consumption, generate various problems of supply and distribution throughout the supply chain. This article evaluates the structure of the mango supply chain in Cundinamarca-Bogota. Using a dynamic model system, the current structure was evaluated in comparison with Lean and Agile supply chains. The structures were measured through the performance indicators of quality, responsiveness, logistic operations and costs. This study showed that the Lean and Agile supply chains improved the performance of the current chain in all cases although not for all the involved actors. However, there was a trade-off that indicated a need for a future evaluation of Agile-Lean structures for perishable fruit chains.